Information systems management in practice - Sprague, Ralph H.; McNurlin, Barbara C. (Prentice Hall, 1993)
This text is intended for use on management information systems courses. It features a comprehensive exploration of how information systems management is being practised by organizations today and offers a business world perspective, providing insights into the issues that chief information officers (CIOs) face as information technology takes on strategic importance in organizations. Emphasis is placed upon the management of information technology rather than the technical aspects, and case studies show how companies are putting information technology to work. Topics covered include business re-engineering, client/server computing, inter-organizational systems, outsourcing, object oriented development, electronic document management, organizational learning and the advances of telecommunications. References are also included to experts and authorities in the field.